Application of the Group Investigation Learning Strategy in Social Studies Subjects at the Elementary Education Level - Syahrani Yumna Irfani (Yayasan Zia Salsabila, 2023)
This study aims to describe the application of group investigation learning strategies to social studies subjects at MI/SD. This study uses a qualitative method, namely research by collecting data from an object by analyzing data that is seen, observed, so that new knowledge and explanations are obtained that are more complex and detailed than something that happened. The results of this study are that the Group Investigation learning strategy can be used in social studies learning. The advantage of the group investigation type cooperative learning strategy is that students can have a good sense of responsibility and students can also individually or in groups discuss to solve problems. The weakness of the group investigation cooperative learning strategy is that this strategy requires many stages, causing little material to be conveyed, this strategy requires a long learning time, and it takes time for students to adjust to this learning strategy, causing the class atmosphere to become tense and tense disturbing the concentration of other students.